Mitochondrial DNA sequence of Culter compressocorpus. (2nd January 2016) - Xu, Min; Tong, Guang-Xiang; Geng, Long-Wu; Jiang, Hai-Feng; Xu, Wei
Abstract: In this study, the complete mitochondrial genome of Culter compressocorpus was detected and annotated. The circular mtDNA molecule was 16, 623 bp in length which contains 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and the non-coding control region (D-loop). Its total protein-coding genes content is 68.67% in whole mitochondrial genome. The mitochondrial genome can contribute to the studies on geographical distribution and genetic diversity of C. compressocorpus resources, as well as molecular phylogeny and species identification in Cyprinidae.